Backlog Perumahan di Kota Yogyakarta sebagai Ancaman Ketahanan Nasional - Muhammad Zaki Mubarrak; Deni Santi Pertiwi; Cesa Carnadi (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The issue of population density that is not matched by adequate housing is a serious problem in Indonesia, and the Yogyakarta region is no exception. This housing backlog cannot be underestimated because of its huge impact on the country and society. Therefore, the government must provide a quick breakthrough to immediately overcome this problem. This research uses empirical normative method. The result of this research is that the population density in Yogyakarta continues to increase every year, while the area in Yogyakarta is limited, so it is not balanced between population and housing, therefore it is necessary to handle such as housing subsidies and the Housing Financing Liquidity Facility (FLPP) scheme.